2011
DOI: 10.3168/jds.2011-4226
|View full text |Cite
|
Sign up to set email alerts
|

Developing a strawberry yogurt fortified with marine fish oil

Abstract: Fortified dairy products appeal to a wide variety of consumers and have the potential to increase sales in the yogurt industry and help increase intake of long-chain n-3 fatty acids. The objectives of this study were to develop a strawberry yogurt containing microencapsulated salmon oil (MSO; 2% wt/vol) and evaluate its characteristics during 1 mo of storage. Unpurified salmon oil (USO) was purified (PSO) and both USO and PSO were analyzed for peroxide value (PV), anisidine value (AV), total oxidation, free fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 35 publications
4
33
1
6
Order By: Relevance
“…Our results are in accordance with the results of Andino (2011), who prepared ω-3 yogurt enriched with salmon fish oil powder and reported a significant reduction of 14.52 % in omega-3 contents after 4 weeks of storage. Similarly, Estrada et al (2011) reported~5.0 and 27.42 % decrease in ALA and DHA content of microencapsulated salmon oil enriched yogurt. It can be calculated from the data that 15 days stored fortified dahi sample had five times higher ALA content than control dahi indicating good oxidative stability of α-linolenic acid in MFOP preparation.…”
Section: Effect Of Mfop Fortification and Storage Time On Texture Promentioning
confidence: 99%
“…Our results are in accordance with the results of Andino (2011), who prepared ω-3 yogurt enriched with salmon fish oil powder and reported a significant reduction of 14.52 % in omega-3 contents after 4 weeks of storage. Similarly, Estrada et al (2011) reported~5.0 and 27.42 % decrease in ALA and DHA content of microencapsulated salmon oil enriched yogurt. It can be calculated from the data that 15 days stored fortified dahi sample had five times higher ALA content than control dahi indicating good oxidative stability of α-linolenic acid in MFOP preparation.…”
Section: Effect Of Mfop Fortification and Storage Time On Texture Promentioning
confidence: 99%
“…However, the milk fat present in dairy products contains high levels saturated fatty acids. Some scientific publications suggest that too much saturated fat in the diet can lead to cardiovascular disease (Estrada et al, 2011;Hu et al, 2001). It would be desirable to enrich dairy products with polyunsaturated fatty acids, which are not synthesized in the human body, and the intake of which from food is often very poor.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of interest in the consumption of omega 3 fatty acids have made it possible to produce food fortified with EPA and DHA from marine sources (Kolanowski and Weiβbrodt, 2007;Rognlien et al, 2012). Because of the fishy flavor which this gives, a good alternative to this is the addition of oils from vegetable sources (Dal Bello et al, 2015;Estrada et al, 2011). The rose hip seed oil is a little-known but rich source of linoleic acid (44.4-55.7%) and α-linolenic acid (18.6-31.4%) in the preferred ratio of 2:1 recommended by dietitians, and it contains only three saturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…Estrada et al (2011) melakukan fortifikasi emulsi minyak ikan pada yoghurt. Fortifikasi dalam bentuk minyak ikan bubuk telah dilakukan pada produk instan (Kalanowski et al 2007).…”
Section: Pendahuluanunclassified
“…Perubahan karakteristik produk selama proses fortifikasi sering terjadi misalnya perubahan karakteristik permen Lozenges (Kalanowski dan Weißbrod 2008), perubahan tingat oksidasi dan warna yoghurt (Estrada et al 2011) (Barrow et al 2009). Produk yang sudah difortifikasi mikrokapsul minyak ikan antara lain permen Lozenges (Kalanowski dan Weißbrod 2008).…”
Section: Pendahuluanunclassified